A Cornerstone of Alachua County’s Economy and Land Base: The Economic Impact of Agriculture and Natural Resources - Rodney L. Clouser; Mohammad Rahmani (EDIS)
FE750, a 12-page report by Rodney L. Clouser and Mohammad Rahmani, provides a profile of agriculture and natural resource industries and an overview of their economic impacts in Alachua County, Florida. The report is based on data from the IMPLAN Pro database for Florida counties for 2006, data from the 2002 Census of Agriculture and data from reports by the Alachua County Property Appraiser. Includes references. Published by the UF Department of Food and Resource Economics, September 2008.